2010
DOI: 10.1097/inf.0b013e3181c40a8a
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between Measles-Mumps-Rubella Vaccination and Autism in Children

Abstract: The study provides evidence against the association of autism with either MMR or a single measles vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 19 publications
0
24
1
2
Order By: Relevance
“…Some of them indicate the role of vaccines as risk factors for autism and others for pervasive developmental disorders. The results of studies did not confirm the association between the MMR vaccination and autism diagnosis [9].…”
Section: Introductioncontrasting
confidence: 45%
“…Some of them indicate the role of vaccines as risk factors for autism and others for pervasive developmental disorders. The results of studies did not confirm the association between the MMR vaccination and autism diagnosis [9].…”
Section: Introductioncontrasting
confidence: 45%
“…The tenth study [8] did not state clearly whether or not the 9 (of 288) children who were not vaccinated against measles were vaccinated against other diseases although the small number of possibly unvaccinated children would not permit a substantive conclusion.…”
Section: Discussionmentioning
confidence: 95%
“…Several large population-and ecologic-based studies were conducted over the following decade that consistently found no evidence of a link between the MMR vaccine and autism and failed to provide any support for Wakefield's theory [24][25][26][27]. In fact, the lack of an association between MMR vaccination and autism in children is supported by 19 additional scientific studies performed by diverse groups of investigators using various research methodologies involving disparate groups of patients over more than a decade [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Several of these studies have been discussed in detail in 4 review articles [47][48][49][50].…”
Section: Lack Of Evidence To Support the "Mmr Causes Autism" Theorymentioning
confidence: 95%
“…Interestingly, in a case-control study conducted in Poland, where the MMR vaccine was introduced later than in most other European countries, the investigators report that the risk of autism was lower in children who received the MMR vaccine than in those who did not [44]. The authors do not claim a "protective" effect of the vaccine, but correctly recognize that the decreased risk of autism among vaccinated children may have been due to other confounding factors in their health status such as, healthcare workers or parents who may have noticed signs of developmental delay or disease before the actual autism diagnosis and for this reason have avoided vaccination [44]. This type of critical and honest analysis is missing from studies that support the contention that the MMR vaccine is associated with ASDs [51][52][53].…”
Section: Lack Of Evidence To Support the "Mmr Causes Autism" Theorymentioning
confidence: 99%